Dehydroepiandrosterone Antagonizes Pain Stress-Induced Suppression of Testosterone Production in Male Rats - Zhu, Qiqi; Ge, Fei; Li, Xiaoheng; Deng, Hou-Sheng; Xu, Miao; Bu, Tiao; Li, Jingyang; Wang, Yiyan; Shan, Yuanyuan; Ge, Ren-Shan; Yao, Ming (Frontiers in Pharmacology, 2018)
Background: Leydig cells secrete the steroid hormone, testosterone, which is essential for male fertility and reproductive health. Stress increases the secretion of glucocorticoid (corticosterone, CORT, in rats) that decreases circulating testosterone levels in part through a direct action on its receptors in Leydig cells. Intratesticular CORT level is dependent on oxidative inactivation of CORT by 11β-hydroxysteroid dehydrogenase 1 (HSD11B1) in rat Leydig cells. Pain may cause the stress, thus affecting testosterone production in Leydig cells. Methods: Adult male Sprague-Dawley rats that orally received vehicle control or 5 or 10 mg/kg dehydroepiandrosterone (DHEA) 0.5 h before being subjective to pain stimulation for 1, 3, and 6 h. In the present study, we investigated the time-course changes of steroidogenic gene expression levels after acute pain induced stress in rats and the possible mechanism of dehydroepiandrosterone (DHEA) that prevented it. Plasma CORT, luteinizing hormone (LH), and testosterone (T) levels were measured, and Leydig cell gene expression levels were determined. The direct regulation of HSD11B1 catalytic direction by DHEA was detected in purified rat Leydig, liver and rat Hsd11b1-transfected COS1 cells. Results: Plasma CORT levels were significantly increased at hour 1, 3, and 6 during the pain stimulation, while plasma T levels were significantly decreased starting at hour 3 and 6. Pain induced stress also decreased Star, Hsd3b1, and Cyp17a1 expression levels at hour 3. When 5 and 10 mg/kg DHEA were orally administered to rats 0.5 h before starting pain stimulation, and DHEA prevented pain-mediated decrease in plasma T levels and the expression of Star, Hsd3b1, and Cyp17a1 without affecting plasma CORT levels. DHEA was found to modulate HSD11B1 activities by increasing its oxidative activity and decreasing its reductive activity, thus decreasing the intracellular CORT levels in Leydig cells. Conclusion: Acute pain caused stress, which inhibited T production in Leydig cells. DHEA protected Leydig cell function from suppression by pain-mediated stress via modulating HSD11B1 activity.